EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVENMENT DIVISION (STAD) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMA NEGERI 1 ANGKOLA SELATAN - Nurhalima Tambunan; Eva Yanti Siregar; Muhammad Syahril Harahap (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2020)
The aim of this study is to describe the effectiveness of using cooperative learning model of STAD type on students’ mathematical solving ability at the tenth grade students of SMA Negeri 1 Angkola Selatan. This research was conducted by applying experimental (one group pre test post test design) with 25 students as the sample and they were taken by using cluster sampling technique from 140 students. Observation and test were used in collecting the data. Based on descriptive analysis, it was found: (a) the average of using STAD type was 3.45 (very good category) and (b) the average of students’ mathematical solving ability before using STAD type was 48.92 (fair category) and after using STAD type was 75.88 (good category). Furthermore, based on inferential statistic by using pair sample ttest, (SPSS version 22), the result showed the significant value was less than 0.05 (0.000<0.05). It means, there is a significant effectiveness of using cooperative learning model of STAD type on students’ mathematical solving ability. By describing of effectiveness of using STAD type was 1) 7.7% students used STAD type enough effectively, 2) 48.6% students used STAD type effectively, 3) 43.7% students used STAD very effectively.